2023
DOI: 10.3389/fmed.2022.1039202
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 disease on the natural course of cirrhosis: Before and after starting vaccination

Abstract: BackgroundCirrhosis has been reported as an important risk factor for death in coronavirus disease 2019 (COVID-19) disease. In this study, we aimed to investigate the effects of COVID-19 on the natural course of cirrhosis before and after starting vaccination.MethodsThe cirrhosis patients in our cohort (n: 140; median age:56; 71 female) were included in this study. The median MELD (Model For End-stage Liver Disease) score was 11 (6–25) and CCI (Charlson Comorbidity Index) score was 4 (1–11). In total, 85 had C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
2
Order By: Relevance
“…Тяжкий гострий респіраторний синдром, спричинений коронавірусом-2 (SARS-CoV-2), та, як наслідок, коронавірусна хвороба 2019 року (COVID-19) стали причиною смерті багатьох людей у всьому світі за останні роки [1]. Як і для SARS-CoV, ангіотензинперетворюючий фермент 2 (АПФ2), що експресується в понад 80 % альвеолярних клітин легень, є чутливим рецептором і для SARS-CoV-2.…”
Section: вступunclassified
See 1 more Smart Citation
“…Тяжкий гострий респіраторний синдром, спричинений коронавірусом-2 (SARS-CoV-2), та, як наслідок, коронавірусна хвороба 2019 року (COVID-19) стали причиною смерті багатьох людей у всьому світі за останні роки [1]. Як і для SARS-CoV, ангіотензинперетворюючий фермент 2 (АПФ2), що експресується в понад 80 % альвеолярних клітин легень, є чутливим рецептором і для SARS-CoV-2.…”
Section: вступunclassified
“…Відомо, що бактеріальні та різні вірусні інфекції мають гірший перебіг у пацієнтів із цирозом печінки (ЦП) порівняно зі здоровою популяцією. COVID-19 у пацієнтів з хронічним гепатитом та ЦП має більш тяжкий перебіг, що пояснюється імунною дисфункцією, яка притаманна для хворих із ЦП [1]. Ураження печінки при COVID-19 може бути пов'язане з прямою цитопатичною дією вірусу, неконтрольованою імунною реакцією, мікро-та макросудинними тромбозами, сепсисом або медикаментозним ураженням печінки.…”
Section: вступunclassified
“…According to already gathered data, it can be assumed that the majority of affected individuals develop a hepatocellular form of injury. It is suggested that a possible background of such a reaction might be related to the similarity between S protein (encoded by the vaccines) and liver-specific proteins [164][165][166][167]. In consequence, autoimmune-like hepatitis might be developed.…”
Section: The Issue Of Vaccination Against Covid-19mentioning
confidence: 99%